UAE-based first-year university students’ perception of lifelong learning skills affected by COVID-19 - Tanju Deveci (Tuning Journal for Higher Education, 2022)
Forcing education institutions to rely on online learning exclusively, the recent pandemic has brought lifelong learning (LLL) to the forefront. The effects of the recent education approaches on students’ LLL skills merit investigation. First-year students may be at a greater risk because of their limited tertiary education experience and universities’ expectations for them to engage in self-directed learning. This study investigated how 38 UAE-based first-year students thought COVID-19 impacted their LLL skills. The quantitative data were collected using a scale while the qualitative data were collected using a reflective task. The results revealed that the students’ overall high score from the scale prior to the pandemic remained stable nine months into it despite a significant decrease in the adaptable learning strategies sub-scale. Yet, some students’ overall LLL scores increased significantly. The qualitative data showed that these students thought they solidified their skills in learning strategies and plans. However, the female students reported a decrease in goal-setting score. Taken together, the results indicate that LLL skills help students reduce the negative impacts of COVID-19 on learning; yet it is still important to note the reducing impact of the pandemic on some students’ skill in adapting learning strategies and setting goals. The results also indicate that LLL skills are malleable and educators can help enhance students’ LLL skills.